Orocardiodigital syndrome: an oral-facial-digital type II variant associated with atrioventricular canal. Issue 5 (May 1996) - Digilio, M C; Marino, B; Giannotti, A; Dallapiccola, B
Abstract : We report on a patient with a constellation of anomalies including hamartomas of the tongue, polysyndactyly, and atrioventricular canal. A similar association has been previously described by Orstavik et al in two sibs. The clinical spectrum of the oralfacial-digital syndrome (OFDS) type II includes all these features. In particular, congenital heart defect, mainly atrioventricular canal, has been described in a few cases. It has been previously suggested that these latter patients may be affected by a variant of OFDS type II. We propose to distinguish this orocardiodigital variant and point out the association of the syndrome with atrioventricular canal.